CTNI-74. PHASE 3 TRIDENT TRIAL: CONCOMITANT RADIATION THERAPY (RT) AND TEMOZOLOMIDE +/- TUMOR TREATING FIELDS (TTFIELDS) IN NEWLY DIAGNOSED GLIOBLASTOMA. (9th November 2020) - Shi, Wenyin; Kleinberg, Lawrence; Jeyapalan, Suriya A; Goldlust, Samuel; Nagpal, Seema; Combs, Stephanie E; Roberge, David; Nishigawa, Ryo; Grossman, Rachel; Glas, Martin
Abstract: BACKGROUND: Tumor treating fields (TTFields) is a non-invasive, regional antimitotic treatment approved as a standard-of-care for newly diagnosed glioblastoma (ndGBM). In the EF-14 Phase 3 trial, TTFields (200 kHz) plus temozolomide (TMZ) significantly increased survival of ndGBM patients without increasing systemic toxicity. TTFields-related AEs were mainly skin AEs. In preclinical models, TTFields increase the therapeutic effects of radiation therapy (RT). A pilot study showed that TTFields concomitant with RT and TMZ is well tolerated. The benefit of concomitant TTFields with RT and TMZ will be tested in the TRIDENT trial. METHODS: TRIDENT is an international phase III randomized trial comparing standard RT with TMZ vs the triple combination of RT/TMZ with concomitant TTFields. RT is delivered through the TTFields arrays. Patients in both arms will receive maintenance TTFields/TMZ. TTFields (200 KHz) will be delivered > 18 hours/day using Optune. Patients will continue TTFields treatment until second recurrence. Patients with pathologically confirmed ndGBM, ≥ 18 years, KPS ≥ 70, either sex, post-surgery or biopsy, and amenable for RT/TMZ therapy will be stratified by extent of resection and MGMT promoter methylation status. The primary endpoint is overall survival (OS). Secondary end points: progression free survival (PFS; RANO), 1- and 2-year survival rates, overall radiological response (ORR; RANO), progression-free survival (PFS6M, PF12M, PFS2Y); severity and frequency of AEs (CTCAE V5.0); pathological changes in resected GBM tumors post treatment; quality of life (EORTC QLQ-C30); and correlation of OS to TTFields compliance. The hypothesis is that concomitant TTFields/RT/TMZ will significantly improve OS versus RT/TMZ. Sample size (N=950; 475/arm) will detect a HR< 0.8 with 5% type I error. Survival will be measured from the time of randomization until date of death. At the time of analysis, patients lost to follow-up or still on protocol follow-up will be censored at the last date known to be alive.